Simulation with Arena - Kelton, W. David. (McGraw-Hill Higher Education, 2007)
This fourth edition of "Simulation with Arena" has the same goal as the first three editions: to provide a comprehensive treatment of simulation concepts in general and the Arena simulation software in particular. It starts by having the reader develop simple, well-animated, high-level models, and then progresses to advanced modeling and analysis. Statistical design and analysis of simulation experiments is integrated with the modeling chapters, reflecting the joint nature of these activities in good simulation studies. The objective is to help the reader carry out effective simulation modeling, analysis, and projects using the Arena simulation system. An informal, tutorial writing style is used to aid the beginner in fully understanding the ideas and topics presented. Included is a CD containing the current version of the Arena academic software and the examples referenced throughout the text.